Assessment of the influence of the acceleration field on scour phenomenon in offshore wind farms. (June 2019) - Escobar, A.; Negro, V.; López-Gutiérrez, J.S.; Esteban, M.D.
Abstract: This paper is the result of research whose main purpose is to analyze the influence of the acceleration field on foundation scour processes in offshore wind farms. The scour phenomenon jeopardizes the operating capacity of offshore structures since it compromises their stability. Up to date, numerous research projects have been carried out to assess scour processes and justify the need for scour protection systems and also to optimize their design. This paper describes the results of an analytical assessment aimed at characterizing, for the first time, the influence of inertial forces on the seabed and on scour by introducing the influence of the acceleration field into the approach to the problem. For this purpose, a specific software for simulating equations in fluid mechanics has been developed. This innovative approach can be used to increase the accuracy of the expected results of the current models to predict foundation scour processes and to improve the whole decision-making process regarding the need for protection systems against scour. Highlights: For the first time, an analysis of the influence of acceleration field on the scour phenomenon, developing a new approach of calculation, has been performed. It includes the comparison of the results by the new approach and the traditional method, with field observations of five European offshore wind farms. The new approach reduces the difference between theoretical and empirical results up to 4.7% depending on the order of non-linearity of the mechanic of waves.